PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Yuni Ovianti; Jul Aidil Fadli (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
The purpose of this study was to determine and analyze the effect of transformational leadership style and work discipline on employee performance in the hormone department of PT Tunggal Idaman Abdi. The number of respondents in this study are 65 people who work in that section. The data analysis method used is Structural Equation Modeling (SEM) PLS. The empirical evidence obtained is from the six hypotheses proposed, five accepted and one rejected. The results of this study found that transformational leadership style and work discipline had a significant effect on job satisfaction, transformational leadership style and job satisfaction had a significant effect on employee performance, but work discipline was not significant on employee performance. The results of the mediation effect test found that the role of job satisfaction significantly mediates the effect of transformational leadership style and discipline on employee performance.